As representações sociais de alunos do ensino fundamental sobre meio ambiente e a questão ambiental nos livros didáticos de geografia - Mendonça., Eliane Maria Barbosa de (2010)
This thesis investigates social representations of the environment by primary school pupils and how school books approach this subject. Our research subjects consisted of the pupils of the Escola Cônego João de Deus. While seeking these representations, we met means of confronting the pupils ideas with the concepts proposed by us (teachers) and by the geography school books. This raises the opportunity of discussing important questions while reflecting upon our teaching practices, as well as a means of validating the need, or lack of it, of working under the perspective of overcoming distorted points of view these pupils have eventually presented throughout the research period, without forgetting that teaching demands respect for the pupils prior knowledge. In order to do so, we have performed a contextualization of the environmental problematic, and we have sought to present the main paradigms that permeate the academic discussion around the concept of environment. From this starting point on, we have tried to explain the relationship between the environment problematic and the need for an environment education able to give solutions to environmental threats. The pupils social representations of the environment were worked upon via open questions, as well as open discussions and the production of drawings. These representations were subject to analysis, then organized as naturalist and anthropocentric, then compared with the school books approach to the environment. We have remarked that in both the social representations and the books, the naturalistic point of view predominates. However, the pupils are very critical regarding environmental problems, positioning themselves as responsible for these problems who may, by changing their attitudes and values, work for the benefit of a sustainable environment.